1989
DOI: 10.1159/000125143
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on the Control of Thyrotropin Secretion by Thyrotropin-Releasing Hormone in the Male Rat

Abstract: Alterations with age in the control of thyrotropin (TSH) secretion by thyrotropin-releasing hormone (TRH) were evaluated at the hypothalamic and pituitary levels in young (3–5 months) and old (22–24 months) male rats. In the hypothalamus, TRH was quantified in the median eminence and in the mediobasal hypothalamus; in the adenohypophysis the membrane receptors for TRH were evaluated as well as the accumulation of TRH in the gland. As for TSH, its concentration was determined in the anterior pituitary gland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
4
11
1
Order By: Relevance
“…FT3 and FT4 serum levels in old rats significantly fall down in comparison with young animals. These results are in line with the findings of Donda et al [15], Cizza et al [24] and Moreira et al [25] who demonstrated a decrease in FT3 and FT4 serum levels in 18-month-old rats. Those authors confirmed a gradual decrease in total T3 and T4 levels with age in rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…FT3 and FT4 serum levels in old rats significantly fall down in comparison with young animals. These results are in line with the findings of Donda et al [15], Cizza et al [24] and Moreira et al [25] who demonstrated a decrease in FT3 and FT4 serum levels in 18-month-old rats. Those authors confirmed a gradual decrease in total T3 and T4 levels with age in rats.…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of literature data it is known that the level of the thyroid hormone falls down, while TSH content is not changed in old rats [15,16]. The biosynthetic activity of the thyroid gland was examined by measuring free thyroxine and triiodothyronine levels, as well as the colloid volume, the percentage of thyroid follicles and the height of secretory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of aging on pituitary deiodinases type 1 and type 2 (D1, D2) is still awaiting further confirmatory studies. Donda and Lemarchand-Beraud found an increase of D1 and deiodinase type 2 (D2) activities in the pituitary of old male rats, while we found both pituitary deiodinase activities to be decreased in the old female rat [36]. No further information seems to be available, although suggestions of a "partial central hypothyroidism" and less efficient response of the hypothalamic-pituitary axis to lower circulating thyroid hormones are found often enough [32].…”
Section: Aging and Hypothalamus-pituitary-thyroid Axiscontrasting
confidence: 50%
“…Hypothalamic TRH content is reduced in aged rats [32,35] and thyrotroph response to TRH is mostly reported as decreased, both in rats [29,32,36] and [37,38] in humans. Non-stimulated TSH concentration has also been reported as relatively diminished by aging in a large population of older persons without hyperthyroidism, and in aging patients with resistance to thyroid hormone (and their non-affected relatives) [27].…”
Section: Aging and Hypothalamus-pituitary-thyroid Axismentioning
confidence: 98%
See 1 more Smart Citation